Clean and sustainable environment problems in forested areas related to recreational activities: case of Lithuania and Turkey - Atalay, Ahmet; Perkumiene, Dalia; Aleinikovas, Marius; Škėma, Mindaugas (Frontiers in Sports and Active Living, 2024)
The aim of this study is to determine the recreational activities organized in forest areas in Turkey and Lithuania, the environmental effects of these activities and the precautions to be taken. In Turkey and Lithuania, interviews were conducted to determine the attitudes of experts involved in recreational activity processes towards a clean environment and environmental sustainability. A semi-structured interview form was used in the interviews with forest operators and other experts. The sample group of the research consists of 17 experts from Turkey and Lithuania. According to the results of the research, recreational activities are organized in forest areas in both countries, but the most important problem related to these activities is waste production. In addition, there is also damage to the natural environment. Although there are legal regulations in both countries, there are no definite results in solving environmental problems. This has a negative impact on the balance between the natural environment and recreation activities. Therefore, a worrying process of environmental degradation is discussed (Marion et al. 2016). It is inevitable to improve the attitudes and behaviors of individuals and to increase environmental awareness and consciousness in order to address these increasing concerns related to human activities (Haukeland et al. 2013). The research is limited to forested areas located in Burdur city in Turkey and forested areas located in Kaunas city in Lithuania. This research was limited to one forest area open to recreation activities in Turkey and Lithuania. Firstly, the fact that the researchers were from Turkey and Lithuania was decisive in the country's limitation. However, Lithuania is a European Union country. Turkey is in the process of membership to the European Union. A clean and safe environment is one of the most important goals of most states and all citizens. Ensuring human rights to a safe and healthy natural environment and environmental protection towards sustainability are among the most relevant and popular socio-economic as well as legal-political issues. With the acceleration of social life, people's interest and demand for forestry recreation activities is increasing. However, with this increase, it is inevitable that negative environmental effects will occur.